2007
DOI: 10.1002/mrd.20842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal circulating cholesterol and gestational diabetes mellitus on lipid metabolism in human term placenta

Abstract: Maternal hypercholesterolemia (HC) during pregnancy and gestational diabetes mellitus (GDM) are associated with disturbance of fetal development which may also modify key features of placental functions. In this study, we evaluated the impact of maternal hypercholesterolemia on placental cholesterol and lipid metabolism in 59 women classified in two groups according to the median concentration of plasma total cholesterol (6.42 mM). The impact of GDM was also evaluated on the metabolism of placentas obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 55 publications
(60 reference statements)
3
57
0
Order By: Relevance
“…31 Furthermore, increased early atherosclerosis markers, such as fatty streaks and lipid peroxidation, in human fetal aorta 5 or in 7-to 14-year-old children 32 born from mothers with TCh level over this cut-off point is reported. Because TCh, HDL-C, and triglyceride plasma by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from levels were unaltered in newborns from women with MSPH, confirming previous observations, 33,34 we speculate on the possibility that MSPH is a pathological condition of the mother coursing with altered human fetoplacental vasculature. A role for LDL-C is suggested in this phenomenon because its maternal plasma concentration was higher in MSPH compared with MPH and because LDL-C is transferred across the placenta.…”
Section: Msph Cut-off Pointsupporting
confidence: 88%
“…31 Furthermore, increased early atherosclerosis markers, such as fatty streaks and lipid peroxidation, in human fetal aorta 5 or in 7-to 14-year-old children 32 born from mothers with TCh level over this cut-off point is reported. Because TCh, HDL-C, and triglyceride plasma by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from levels were unaltered in newborns from women with MSPH, confirming previous observations, 33,34 we speculate on the possibility that MSPH is a pathological condition of the mother coursing with altered human fetoplacental vasculature. A role for LDL-C is suggested in this phenomenon because its maternal plasma concentration was higher in MSPH compared with MPH and because LDL-C is transferred across the placenta.…”
Section: Msph Cut-off Pointsupporting
confidence: 88%
“…Similarly, maternal cholesterol has been reported as increased (17) or unchanged (14,18,19) across gestation. Studies in women with GDM have shown no difference (18) or a decline in LDL-C concentration (20) but with increased levels of small, dense LDL (18,20) and increased LDL oxidation (17).…”
Section: Gdmmentioning
confidence: 94%
“…Genes for lipid metabolism and those for inflammatory pathways are upregulated in the placenta of women with GDM (2). This upregulation increases or unbalances production of inflammatory cytokines and energy metabolism regulatory cytokines such as adipokines (2,6,7), which increases adiposity at birth (8,9) and predisposes the newborn to become overweight and develop metabolic diseases such as impaired glucose tolerance, metabolic syndrome, and cardiovascular disease (2,(6)(7)(8). Previous studies have focused on the pathophysiologic pathways and cytokine levels in GDM and their possible effect on offspring comorbidities later in life (1,6,7,10).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%